Varying proliferative and clonogenic potential in NRAS‐mutated congenital melanocytic nevi according to size. Issue 10 (October 2016) - Guégan, Sarah; Kadlub, Natacha; Picard, Arnaud; Rouillé, Thomas; Charbel, Christelle; Coulomb‐L'Hermine, Aurore; How‐Kit, Alexandre; Fraitag, Sylvie; Aractingi, Selim; Fontaine, Romain H.
Abstract: Congenital melanocytic nevi (CMN) are benign proliferations that may be associated with various consequences depending on their size. They are characterized by a specific molecular signature, namely a postzygotic somatic NRAS or BRAF mutation. We have recently reported that large CMN (lCMN), which are classically associated with an increased melanoma risk, harbour cell subpopulations with specific clonogenic and tumorigenic potential. We wished to ascertain whether cells displaying similar properties persisted postnatally in medium CMN (mCMN). Eighteen medium M1, nine large and one giant NRAS ‐mutated CMN were prospectively included in the study. Subpopulations of mCMN cells expressed stem cell/progenitor lineage markers such as Sox10, nestin and Oct4, as was the case in lCMN. Nevertheless, conversely to lCMN, mCMN cells with clonogenic properties were rarer. In vitro, approximatively one in 1500 cells isolated from fresh mCMN formed colonies that could be passaged. In vivo, mCMN seemed to harbour cells with less proliferative potential than the larger lesions as lCMN biopsies displayed a threefold expansion compared to mCMN when xenografted in Rag2 −/− mice. Thus, our data revealed variations in clonogenicity and tumorigenic properties in NRAS ‐mutated CMN according to size.